Prevalence and impact of PCR artifacts from soil samples using the Applied Biosystems™ GlobalFiler™ PCR amplification kit: Interference of non-human artifacts in DNA profiles from a homicide investigation. Issue 1 (December 2019) - Diegoli, Toni M.; Moore, Tyiesha; Weitz, Steven; Bille, Todd W.
Abstract: Non-human artifacts have been observed in a range of forensic typing methods. This is primarily due to the condition and potential environmental contamination of many evidentiary samples. Here, a case example of non-human artifact peaks is presented to illustrate ways in which to recognize potential artifact peaks as well as mitigate their effect on interpretation.